Safety Issues in Lithium Ion Batteries: Materials and Cell Design - Wu, Xiangkun; Song, Kaifang; Zhang, Xiaoyan; Hu, Naifang; Li, Liyuan; Li, Wenjie; Zhang, Lan; Zhang, Haitao (Frontiers in Energy Research, 2019)
As the most widely used energy storage device in consumer electronic and electric vehicle fields, lithium ion battery (LIB) is closely related to our daily lives, on which its safety is of paramount importance. LIB is a typical multidisciplinary product. A tiny single cell is composed of both organic and inorganic materials in multi scale. In addition, its relatively closure property made it difficult to be studied on line, let alone in the battery pack or system level. Safety, often manifested by stability on abuse, including mechanical, electrical and thermal abuses, is a quite complicated issue of LIB. Safety has to be guaranteed in large scale application. Here, safety issues related to key materials and cell design techniques will be reviewed. Key materials, including cathode, anode, electrolyte and separator, are the fundamental of the battery. Cell design and fabrication techniques also have significant influence on the cell’s electrochemical and safety performances. Here, we will summarize the thermal runaway process in single cell level, and some recent advances on battery materials and cell design.